GOOD CORPORATE GOVERNANCE (GCG) PRINCIPLE IN SHARIA BANKING: AN ISLAMIC LAW PERSPECTIVE - Suryani, Suryani; Faisal, Yudi Ahmad; Fathoni, Muhammad Anwar; Santoso, Lukman (International Journal of Law Reconstruction, 2021)
The implementation of Islamic economy in Indonesia is due to the fact that Islam has a comprehensive and universal teaching in all human life aspects, including economy. One encouraging Islamic banking development in Indonesia is indicated by the operation of banks accommodating the Sharia principles. The rapid development of Sharia banking requires an immediate implementation of Good Corporate Governance (GCG) System to provide a maximum protection for the stakeholders, especially customers. The implementation of GCG is expected to help Sharia banking minimize the poor financing quality, increase the bank assessment accuracy, infrastructure, and business decision making quality as well as become the early detection to high risk business areas, products, and services. The implementation of GCG system is greatly important since Sharia banking is the intermediary institution requiring the public or stakeholders’ trust.